Modeling and Dynamics Analysis Belt Drive in Planetary Transmission System - Qi Xuemei (Jixie chuandong)
For the problem of planetary transmission system that the complex system structure in the course of using,high manufacture precision and limitations strong during long-distance power transmission process.According to the traditional characteristics of the planetary transmission system,a new planetary transmission system includes belt drive is established,and its kinematics and dynamics modeling are carried out.Finally,the impact law of the main parameters of the system of ratio,structure size on the system operating characteristics are studied.Research shows that,a certain guiding significance for the design of belt drive in planetary transmission system is provided.